Wearable Art as an Experimental Entrance to Designing Expressive Outfits on a Mannequin Inspired from the Architectural Heritage of the Kingdom of Saudi Arabia - Dalal Alshareef (Journal of Architecture, Art & Humanistic Science, 2021)
This research aims to study the possibility of designing expressive fashion on the mannequin as a wearable art inspired by the architectural heritage of of Saudi Arabia using recycled materials, to find new artistic features characterized by originality and modernity, and highlighting the artistic and aesthetic features of heritage buildings according to each region with an expressive technical nature compatible with the art Fashion design. The research followed the descriptive analytical method in studying the concept of wearable art, its beginnings and its historical and creative development, and in analyzing and describing the styles of traditional buildings in Saudi Arabia:1- Hijaz style (Hijaz house - Hijaz palaces)2- Najdi style (Najdi House - Al-Duryia Buildings)3- The Southern style (Asiri House - Al Asha Al Jawizah)In addition to the applied study that resulted in eight designs of expressive costumes on the mannequin as a wearable art that mimics the architectural heritage of Saudi Arabia with recycled materials and materials (paper - cardboard - fabric scraps - stones - wood - buttons - threads - burlap - wicker).The arbitrators agreed that the designs are actual applications of wearable art, and clearly indicate the traditional buildings borrowed from them. The relationship between wearable art and heritage is also present to reflect the diversity of cultures, geographical locations, nature and human mood in past times.The research recommended organizing local art competitions between universities in the field of wearable fashion and arts, and then elevating them to international partnerships, and taking advantage of historical study to stimulate this type of arts and support it commercially in exhibitions and events and scientifically by including it in the curricula and scientific research.